The changing nature of financial intermediation and the financial crisis of 2007-09 - Tobias Adrian; Hyun Song Shin (Federal Reserve Bank of New York, 2010)
The financial crisis of 2007-09 highlighted the changing role of financial institutions and the growing importance of the shadow banking system, which grew out of the securitization of assets and the integration of banking with capital market developments. This trend was most pronounced in the United States, but it also had a profound influence on the global financial system as a whole. In a market-based financial system, banking and capital market developments are inseparable, and funding conditions are tied closely to fluctuations in the leverage of market-based financial intermediaries. Balance-sheet growth of market-based financial intermediaries provides a window on liquidity by indicating the availability of credit, while contractions of balance sheets have tended to precede the onset of financial crises. We describe the changing nature of financial intermediation in the market-based financial system, chart the course of the recent financial crisis, and outline the policy responses that have been implemented by the Federal Reserve and other central banks.
Keywords: E02; E58; G10; G18; 330; Financial crisis; financial intermediation; intermediation chains; procyclicality; liquidity facilities; monetary polic; Finanzmarktkrise; Finanzintermediär; Kreditmarkt; Bankbilanz; Bilanzstrukturmanagement; Geldpolitik; USA